Hydrotropic polymeric mixed micelles based on functional hyperbranched polyglycerol copolymers as hepatoma‐targeting drug delivery system. Issue 1 (6th November 2012) - Zhang, Xuejiao; Zhang, Xinge; Yu, Peien; Han, Yucai; Li, Yangguang; Li, Chaoxing
Abstract Mixed copolymer nanoparticles (NPs) self‐assembled from β‐cyclodextrin‐grafted hyperbranched polyglycerol (HPG‐g‐CD) and lactobionic acid (LA)‐grafted hyperbranched polyglycerol (HPG‐g‐LA) were applied as carriers for a hydrophobic antitumor drug, paclitaxel (PTX), achieving hepatocellular carcinoma‐targeted delivery. The resulting NPs exhibited high drug loading capacity and substantial stability in aqueous solution. In vitro drug release studies demonstrated a controlled drug release profile with increased release at acidic pH. Remarkably, tumor proliferation assays showed that PTX‐loaded mixed copolymer NPs inhibited asialoglycoprotein (ASGP) receptor positive HepG2 cell proliferation in a concentration‐dependent manner in comparison with ASGP receptor negative BGC‐823 cells. Moreover, the competition assay demonstrated that the small molecular LA inhibited the cellular uptake of the PTX‐loaded mixed copolymer NPs, indicating the ASGP receptor‐mediated endocytosis in HepG2 cells. In addition, the intracellular uptake tests by confocal laser scanning microscopy showed that the mixed copolymer NPs were more efficiently taken up by HepG2 cells compared with HPG‐g‐CD NPs. These results suggest a feasible application of the mixed copolymer NPs as nanocarriers for hepatoma‐targeted delivery of potent antitumor drugs. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:145–153, 2013